The Different Analysis of Carbon Footprint according to Life Cycle Assessment of Furniture Type: A case study of the Table - Karuna Kwangsawat; Yanin Rugwongwan (My University, 2017)
This article attempts to present the process of preparing an analysis on differential Carbon Footprint of each furniture types according to their product life cycle. The case study on one type of furniture namely "Tables" is to assessment the environmental effect of the production process and the method of raw material selection in furniture manufacturing and by using carbon footprint is an indicator of its effect. By using different types of furniture and product grouping furniture to indicate and calculate the quantity of carbon footprint. During the study customer's perception in response to environmentally friendly products, the result is expected to be the quantity of carbon footprint could be classified into three levels, i.e. furniture with the high, the medium and the low level of carbon footprints.Keywords: Carbon Footprint; Life Cycle Assessment, Furniture Design, Environmental.ISSN: 2398-4287© 2017. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.
Keywords: Carbon Footprint; Footprint; Table (database); Material Selection and Properties